Human macrophage-engineered vesicles for utilization in ovarian cancer treatment - Schweer, David; Anand, Namrata; Anderson, Abigail; McCorkle, J. Robert; Neupane, Khaga; Nail, Alexandra N.; Harvey, Brock; Hill, Kristen S.; Ueland, Frederick; Richards, Christopher; Kolesar, Jill (Frontiers in Oncology, 2023)
Ovarian cancer is a deadly female malignancy with a high rate of recurrent and chemotherapy-resistant disease. Tumor-associated macrophages (TAMs) are a significant component of the tumor microenvironment and include high levels of M2-protumor macrophages that promote chemoresistance and metastatic spread. M2 macrophages can be converted to M1 anti-tumor macrophages, representing a novel therapeutic approach. Vesicles engineered from M1 macrophages (MEVs) are a novel method for converting M2 macrophages to M1 phenotype-like macrophages. Methods: Macrophages were isolated and cultured from human peripheral blood mononuclear cells. Macrophages were stimulated to M1 or M2 phenotypes utilizing LPS/ IFN-γ and IL-4/IL-13, respectively. M1 MEVs were generated with nitrogen cavitation and ultracentrifugation. Co-culture of ovarian cancer cells with macrophages and M1 MEVs was followed by cytokine, PCR, and cell viability analysis. Murine macrophage cell line, RAW264.7 cells were cultured and used to generate M1 MEVs for use in ovarian cancer xenograft models. Results: M1 MEVs can effectively convert M2 macrophages to an M1-like state both in isolation and when co-cultured with ovarian cancer cells in vitro, resulting in a reduced ovarian cancer cell viability. Additionally, RAW264.7 M1 MEVs can localize to ovarian cancer tumor xenografts in mice. Conclusion: Human M1 MEVs can repolarize M2 macrophages to a M1 state and have anti-cancer activity against ovarian cancer cell lines. RAW264.7 M1 MEVs localize to tumor xenografts in vivo murine models.